52 degrees south: mental health services in the Falkland Islands. (19th April 2018) - Rimicans, Karen; McInerny, Tim
Abstract : This article discusses the factors that have shaped the development of the new mental health legislation within the Falkland Islands. The process of implementing new legislation within this remote island community is discussed, including the aspirations underlying the new legislation, the management of psychiatric emergencies and the needs of the clinical team.